2007
DOI: 10.1002/chem.200700351
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Perhydropolysilazane into a SiOx Network Triggered by Vacuum Ultraviolet Irradiation: Access to Flexible, Transparent Barrier Coatings

Abstract: The photochemical conversion of 200-500 nm layers of perhydropolysilazane --(SiH2-NH)n-- (PHPS) in the presence of oxygen into an SiOx network was studied. Different UV sources in the wavelength range of 160-240 nm, that is, 172 nm Xe2* and 222 nm KrCl* excimer, and 185 nm Hg low-pressure (HgLP) lamps were used for these purposes. The role of both ozone and O(1D) as well as of catalytic amounts of tertiary amines in the degradation process of PHPS and the formation of SiOx were studied. In this context, the ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 34 publications
(39 reference statements)
2
98
0
2
Order By: Relevance
“…Naganuma et al 20) reported that oxidation reactions were dominant as compared with dissociation of bonds by VUV irradiation. Prager et al 21) reported, on the other hand, that dissociation of bonds was much faster than oxidation reactions, and they thus concluded that dissociation of bonds was preferable. They suggested that SiN bonds were directly cleaved by VUV light.…”
Section: ¹1mentioning
confidence: 99%
See 1 more Smart Citation
“…Naganuma et al 20) reported that oxidation reactions were dominant as compared with dissociation of bonds by VUV irradiation. Prager et al 21) reported, on the other hand, that dissociation of bonds was much faster than oxidation reactions, and they thus concluded that dissociation of bonds was preferable. They suggested that SiN bonds were directly cleaved by VUV light.…”
Section: ¹1mentioning
confidence: 99%
“…Thus, volume increase instead of volume shrinkage could be expected upon the conversion. 21) These considerations suggest that the conversion of PHPS into silica coating via VUV irradiation is advantageous for reducing the number of both macro-size and molecular-size defects.…”
Section: ¹1mentioning
confidence: 99%
“…However, this energy still exists the risk for Si-O (4.68 eV) bonds dissociation afterwards. Prager et al also mention that VUV photon triggers the Si-N bond dissocation and accelerates the conversion rate of PSZ [4]. Moreover, the similar phenomena of VUV-induced of organsiliazanes into methyl-Si-O-Si networks also was demonstrated by Knolle et al [14].…”
Section: Resultsmentioning
confidence: 68%
“…Polysilazane-based SOG (PSZ-SOG), (SiH 2 NH) n , has been widely used in shallow trench isolation (STI), inter-layer dielectric (ILD), and pre-metal dielectric (PMD) layers owing to its excellent gap-filling ability, low moisture absorption, and high etch resistance [1][2][3][4]. A following higher thermal curing in the furnace (420-1050 °C) is essential for better PSZ conversions, denser oxide film, and good isolation performance [5][6].…”
Section: Introductionmentioning
confidence: 99%
“…1. Prager et al [37] pioneered the research on the mechanism of ultraviolet irradiation conversion method. They demonstrated the high-energy UV photons can excite the Si-N bond breakage.…”
mentioning
confidence: 99%